Diabetic Gastroparesis: Diagnosis, Management, and Future Perspectives - Dołęga, Marcin; Dróżdż, Olgierd; Gacka, Piotr; Musialska, Dominika; Gołda, Joanna; Mężyk, Julia; Snopkowska, Aleksandra (Quality in Sport, 2024)
Gastroparesis, a complication of diabetes, is characterized by delayed gastric emptying without obstruction. It arises from chronic hyperglycemia-induced damage to the autonomic and enteric nervous systems, manifesting primarily as nausea, vomiting, early satiety, and bloating. This condition severely impacts quality of life and glycemic control, increasing the risk of further diabetes-related complications. Early diagnosis and treatment are essential, involving stringent glycemic control, lifestyle changes, pharmacological therapy, and sometimes surgical interventions. Diagnostic approaches include ruling out other causes, followed by tests like scintigraphy, radiological examination, and breath tests. Treatment begins with dietary modifications and, if necessary, progresses to enteral or parenteral nutrition. Glycemic management is crucial, with specific medications either recommended or contraindicated. Pharmacological treatments include metoclopramide and domperidone, though both have significant side effects. Emerging therapies involve ghrelin and motilin agonists, and antidepressants like mirtazapine. Gastric electrical stimulation, endoscopic, and surgical procedures offer additional treatment avenues for severe cases. Effective management of gastroparesis can substantially improve patient outcomes and long-term diabetes management.